2022
DOI: 10.1002/pen.26158
|View full text |Cite
|
Sign up to set email alerts
|

Smart polydimethylsiloxane sponges with high piezoelectric responses

Abstract: In recent years, soft and stretchable electrets have drawn considerable attention for their wide applications in energy harvesters, sensors, and actuators. However, existing electrets struggle to attain both longevity and stretchability (softness), which means charge retention capability and stretchability (softness) of electrets conflict. In this article, one novel soft and stretchable electret (PPSE) with great electromechanical performance is demonstrated. The PPSE is composed of a polydimethylsiloxane (PDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The combination of Ecoflex matrix and ePTFE gives rise to the improved comprehensive mechanical properties of the composite electret because of the excellent stretchability, low elastic modulus, and low hysteresis of Ecoflex elastomer ( Figure S5b,e ). In comparison with the recently reported research [ 5 , 6 , 9 , 17 , 20 , 22 , 26 ], the ePTFE/Ecoflex composite electret exhibits superior performance in terms of stretchability and longevity. Therefore, a composite electret with longevity, high charge density, and robust comprehensive mechanical properties is achieved, which can be potentially applicable to constructing self-powered flexible electronic devices.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The combination of Ecoflex matrix and ePTFE gives rise to the improved comprehensive mechanical properties of the composite electret because of the excellent stretchability, low elastic modulus, and low hysteresis of Ecoflex elastomer ( Figure S5b,e ). In comparison with the recently reported research [ 5 , 6 , 9 , 17 , 20 , 22 , 26 ], the ePTFE/Ecoflex composite electret exhibits superior performance in terms of stretchability and longevity. Therefore, a composite electret with longevity, high charge density, and robust comprehensive mechanical properties is achieved, which can be potentially applicable to constructing self-powered flexible electronic devices.…”
Section: Resultsmentioning
confidence: 57%
“…Although both stretchability and longevity were achieved in this electret film, the strain and stretch direction also restrict its applications. A straightforward approach has been proposed to improve the longevity of elastomer electrets, which is to introduce the inorganic nanoparticles or hard plastic nanoparticles, e.g., silica nanoparticles [ 9 ] and PTFE nanoparticles [ 22 ], into the elastomer matrix. Suo et al [ 9 ] reported a stretchable electret based on silica nanoparticles filled polydimethylsiloxane, which provided a charge density of 4 × 10 −5 C m −2 and a lifetime beyond 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Sugar, crystal salts, and oxides have been used as templates. [16][17][18][19][20] The use of ZnO nanoparticles as templates appears as an interesting possibility since it has been reported as template for triboelectric nanogenerators [16] and, but its application as generators of pores for sponges has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%